Synthesis of the unusual lipid bis(monoacylglycero)phosphate in environmental bacteria. (28th September 2021) - Czolkoss, Simon; Borgert, Pia; Poppenga, Tessa; Hölzl, Georg; Aktas, Meriyem; Narberhaus, Franz
Summary: The bacterial membrane is constantly remodelled in response to environmental conditions and the external supply of precursor molecules. Some bacteria are able to acquire exogenous lyso‐phospholipids and convert them to the corresponding phospholipids. Here, we report that some soil‐dwelling bacteria have alternative options to metabolize lyso‐phosphatidylglycerol (L‐PG). We find that the plant‐pathogen Agrobacterium tumefaciens takes up this mono‐acylated phospholipid and converts it to two distinct isoforms of the non‐canonical lipid bis(monoacylglycero)phosphate (BMP). Chromatographic separation and quadrupole‐time‐of‐flight MS/MS analysis revealed the presence of two possible BMP stereo configurations acylated at either of the free hydroxyl groups of the glycerol head group. BMP accumulated in the inner membrane and did not visibly alter cell morphology and growth behaviour. The plant‐associated bacterium Sinorhizobium meliloti was also able to convert externally provided L‐PG to BMP. Other bacteria like Pseudomonas fluorescens and Escherichia coli metabolized L‐PG after cell disruption, suggesting that BMP production in the natural habitat relies both on dedicated uptake systems and on head‐group acylation enzymes. Overall, our study adds two previously overlooked phospholipids to the repertoire of bacterial membrane lipids and provides evidence for the remarkable condition‐responsive adaptation of bacterial membranes.